The influences of Abraham Maslow's Hierarchy of Needs Theory, Field Practice Experience, and 21st Century Skills on Career Choice of Becoming a Vocational Teacher - Mauluddiyah, Atikah (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The needs of being vocational teachers is still very high. One of the factors that mostly causes students' reluctance to choose a career as a teacher is the unfulfilled needs based on Abraham Maslow's hierarchy to become a vocational teacher. Another factor is implementing field experience practice and preparing 21st century skills for prospective teachers of the Vocational High School. This study aimed at determining the effects of Abraham Maslow's hierarchy of needs, field experience practice, and 21st century skills on career choices to become vocational teachers on the state university students of Informatics Engineering Education in Malang City. A correlational approach with a sample of 123 students was used in this study. The results of the multiple regression analysis showed that Abraham Maslow's hierarchy of needs, field experience practice, and 21st century skills had an influence of 0.515 or 51.5 percent on career choice to become the vocational teacher. It is concluded that there is an influence between of three factors and the career choice to become vocational teachers.